Regionális hulladékszállítás Magyarországon - Dienes, Tamás (Közép-Európai Közlemények, 2010)
Hungary is constructing several regional waste management projects which are cofinanced from the European Union grants (formerly ISPA, presently: Cohesion Fund). The project area of these regional projects are mainly determined by the consulting companies and the relevant municipalities. However, these programmes do not take into consideration the present waste management plans and so at many cases it can happen that a landfill site is located very close to another landfill site which are at the borders of two, independently operating regional waste management project areas. It can be also stated that the statistical waste management plans are not in line with the national waste management plan (these are being reviewed at the moment) and the Cohesion Fund new regional waste management plans do not follow the statistical waste management plans as the borders of them are also different. This article briefly describes the present situation of the construction of the regional waste management plans, the neccessary facilities in a regional waste management plan as well as the logistics of the waste management transport in the EU cofinanced regional waste management projects.